Validity of instrument to measure mathematics teachers’ perceptions towards problem-based learning activities - Mohamad Ikram Zakaria; Mohd Fadzil Abdul Hanid; Roslizam Hassan (International Journal of Evaluation and Research in Education (IJERE), 2024)
Problem-based learning (PBL) is a proposed method for teaching mathematics in primary education in the education 4.0 era. This method enables teachers to conduct effective instruction by allowing students to explore alternative solutions to problems. This study was conducted to develop and validate an instrument for evaluating primary school mathematics teachers’ perceptions of PBL activities. This research is quantitative, and a questionnaire was employed to collect data. The data obtained were analyzed descriptively utilizing Cronbach’s alpha and exploratory factor analysis (EFA). It is determined that Cronbach’s alpha is 0.885, with a factor eigenvalue greater than 1. The Kaiser–Meyer–Olkin (KMO) value for each construct is 0.50, whereas Bartlett’s test value is statistically significant (<0.5). Each item has a factor loading of 0.50 or higher and a standard deviation of ≥60%. This study’s results indicated that this instrument can be used to investigate primary school mathematics teachers’ perceptions of PBL activities involving group division, generating ideas and learning issues, identifying problems, self-directed learning, synthesis and application, reflection, and assessment.